Tick-borne encephalitis: pathogenesis and clinical implications - Růžek, Daniel; Dobler, Gerhard; Donoso Mantke, Oliver (Travel medicine and infectious disease, 2010)
Tick-borne encephalitis (TBE) is an important and severe neurological illness occurring in large areas of Europe and northern Asia. Only a small proportion of those infected develop clinical symptoms. The symptomatic cases are, however, characterized with fevers and debilitating encephalitis that might progress into chronic disease or fatal infections. This review summarizes data on clinical presentation, pathogenesis and pathology of TBE in humans, and of experimental TBE in animal models with the purpose to explain why is TBE such a severe disease clinically.
Keywords: modely nemocí na zvířatech; klíště; Child; dítě; Adult; Encephalitis Viruses, Tick-Borne; dospělí; Encephalitis, Tick-Borne; Viral Vaccines; Animals; lidé; Humans; zvířata; klíšťová encefalitida; Disease Models, Animal; myši; Ixodes; viry klíšťové encefalitidy; Mice; virové vakcíny